In- vitro study to evaluate the antibacterial activity of Seethodaka, Visarpahara and Neelyadi oil against Staphylococcus aureus and Escherichia coli: Molligoda S.P.1*, Thiripuranatharb G.2, Rathnayaka R.L.Y.U.1, Arachchi K.R.A.1 and Aththanayaka A.M.S.2 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2023)
Ayurvedic and traditional oil plays a major role in internal and external treatment for numerous diseases as well as wellness in Ayurveda. Ayurvedic studies have gifted thousands of oil recipes with dynamic applications. Seethodaka, Neelyadi, and Visarpahara are some of the commonly available traditional oils which show wondering effects in treating skin diseases such as ulcers, wounds, rashes and boils. Staphylococcus aureus and Escherichia coli are the widely detected bacteria in skin conditions. This study conveys the determination of antimicrobial effects of Seethodaka, Visarpahara, and Neelyadi oils against Staphylococcus aureus and Escherichia coli using standard antibiotic sensitivity tests. Microbial assays were conducted using Mueller Hinton Agar medium. Five wells were made in each plate, and the bottom was sealed using molten agar. Tetracycline or Azithromycin and DMSO were used as positive and negative controls, respectively. The zone of inhibition was measured after incubation at 37°C for 24 hours. Each assay was done in triplicate and the average zone of inhibitions was calculated. The results exhibit an inhibition diameter of 12 mm for Seethodaka oil against Staphylococcus aureus while 16 mm for Visarpahara oil and 13 mm for Neelyadi oil against the same bacteria. The positive controller, Tetracycline, shows a 40mm inhibition zone diameter against Staphylococcus aureus. According to the results, all three oils have a considerable antimicrobial effect against Staphylococcus aureus. Also, 8mm of inhibition zone diameter shows for Seethodaka oil for Escherichia coli, and there is an incredible antimicrobial effect shown by Visarpahara oil against Escherichia coli with an inhibition zone diameter of 24 mm. Neelyadi oil also has a considerable inhibition zone diameter (12mm) against Escherichia coli. The inhibition zone diameter of the positive controller against Escherichia coli is 30mm. Therefore, it can be concluded that all three tested traditional oils have considerable antibacterial effects against Staphylococcus aureus and Escherichia coli. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">